PERLINDUNGAN HUKUM TERHADAP PENUMPANG PENYANDANG DISABILITAS DALAM AKSESIBILITAS TRANSPORTASI PUBLIK PADA BUS TRANS METRO BANDUNG - Yoshi Pins Yolando; Aji Wibowo (Fakultas Hukum Universitas Tarumanagara, 2020)
Everyone has the same rights before the law based on the principle of equality before the law, that everyone has equal rights in law without exception. This principle is used to obtain equality such as persons with disabilities. Protection of persons with disabilities must provide guarantees in the form of facilities (accessibility). However, the bus in Bandung like Trans Metro Bandung (TMB) still doesn’t provide convenience. How is the legal protection for passengers with disabilities in the accessibility of public transportation on TMB buses and how the Bandung City Government's efforts towards accessibility for passengers with disabilities. This research was conducted by legal research methods for academic purposes. The author's research results show that accessibility of TMB bus’s activities is still not fulfilled. The understanding of persons with disabilities in Bandung is still too narrow, that is only wheelchair-friendly, so the accessibility is provided only to wheelchair users and the efforts of the Bandung City Government are establishing regional regulation as a form of seriousness of the Bandung City Government to protect the rights of persons with disabilities. The government must provide the same treatment by providing accessibility that can be used by everyone so that equality of opportunity is realized.